Makna simbolik upacara kematian di Gorontalo perspektif Karl Jaspers - Nazar Husain Hadi Pranata Wibawa; Septiana Dwiputri Maharani; Hardono Hadi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
The focus of this article is to examine the symbols used in funeral ceremonies from Gorontalo in the perspective of Karl Jaspers' human philosophy. This research is a library research supported by field research. Literature research uses library data collection methods, while field research uses observation, participatory, interview. Data analysis uses interpretation, historical, heuristic and reflection. The research finds interpretations and reflections on the symbolism of the ceremonial tradition showing that it is not only a chiffer, but a chiffer that gives the power of revelation to other chiffers and unites them in Divine reality. The tradition illustrates that every element of reality, history and culture is interrelated and reveals elements of the same divinity, uborampe and media in ceremonies are symbols towards the Transcendent and play a role in life. The symbols used in the tradition illustrate that every divine power and element in the entire cosmos is in the unity of divinity.